The moderating effect of generations on the relationship between work values and affective commitment - Gugup Kismono; Wulandari (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
Purpose –This study compared Generation X and Y's work values and affective commitment and explored if generation moderates the relationship. This research is needed to elucidate generational disparities in work values, affective commitment, and work values' impact on affective commitment. Validating the global generation theory requires research involving Indonesians from different industries. Design/methodology/approach – Data was acquired from 630 self-administered questionnaires from various businesses. The instruments used to measure variables have a track record of validity and reliability and were adapted from that work. The Chow Method was used to calculate the generational influence on affective commitment. Findings – The results demonstrated that Generation X and Generation Y in Indonesia had similar work values but differing affective commitment. Generation moderates the association between work values and affective commitment. This research reveals individuals with various life circumstances may still exhibit distinct character traits and value systems. Research limitation/implications – The data may not capture the traits of all generations. Generalizations must be done with caution. Generation X and Y participants were not distributed proportionally. Prior research showed that the proportion of participants didn't alter the results, but future research may take distribution into account. Practical implications – Job sector classifications and job characteristics that are suitable for Generation X and Generation Y can be developed by considering the generations' unique preferences for various value components of employment. Originality/value – This study added to our understanding of how different generations approach and value work in different ways. The implications of this study's findings for confirming the global theory of generation regarding work values and affective commitment are substantial. The results of this research demonstrated the importance of taking cultural factors into account while dealing with employees of varying ages.